History of Art: A Chain of Movements and Counter-movements - Sharma, Yam Prasad (Achyutram Bhandari Sangit Pratisthan Aalekh, 2025)
Art movements and counter movements are appearing and disappearing in terms of shared-ness and innovation throughout the history of art. Existing trends and techniques in the mainstream are questioned by the new experiments in arts. New ways of creation put organized effort to break away from the earlier movement. This is called counter movement. The new art trend sometimes partially shares from the earlier one and sometimes completely opposes the existing style. In some cases, history reappears in renewed form with new relevance. There is not only departure but also connection. After a long period of time, the old fashion appears to be new. Beauty, aesthetic and taste of art are changing. Hence, art forms and presentations are changing. The new trend innovative and creative. The new insights in the creator bring a departure. New perspectives provide new aesthetic experience to the viewer. When the same techniques are repeated for long period, the works become ordinary like daily commodities. Great artists break the established boundaries and codes. Change, departure and reconnection are the significant elements are movements.